INTEGRASI PASAR KAKAO INDONESIA DAN DUNIA - , ELIYATININGSIH, Prof. Dr. Ir. Dwidjono Hadi Darwanto, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Indonesia is the third largest producer and exporter of cocoa in the world market. Over the last thirty years Indonesia has been routinely done in the form of exports of cocoa beans and its processed products. Thus, it is important to assess the efficiency of the cocoa trade on the world market through price analysis. Prices can be an indicator of the market performance and efficiency. This research was aimed to (1) determine the factors that influence Indonesian cocoa price